The growth of early social networks: New geochemical results of obsidian from the Ubaid to Chalcolithic Period in Syria, Iraq and the Gulf. (October 2016) - Khalidi, Lamya; Gratuze, Bernard; Stein, Gil; McMahon, Augusta; Al-Quntar, Salam; Carter, Robert; Cuttler, Richard; Drechsler, Philipp; Healey, Elizabeth; Inizan, Marie-Louise; Mouralis, Damase; Pernicka, Ernst; et al.
Abstract: Obsidian artifacts are geochemically traceable to their geological sources of origin. The results of their analysis provide some of the most accurate testimonies of interaction, exchange and population movement. This article presents results of obsidian analyses of artifacts from twelve sites from the Middle Euphrates to the Arabian Gulf. We demonstrate that the Sıcaksu flow of Nemrut Dağ in eastern Turkey consistently supplied obsidian to the majority of sites across this region from the 7th to 4th millennia BCE. This outcrop predominated in analyzed assemblages and as a production material for the region, across all site positions, sizes and periods; this has been argued to be a result of the quality, quantity and accessibility of this flow (Robin et al., 2016 ). The analyses demonstrate the presence of mainly finished products from a variety of additional sources in eastern Anatolia and Armenia (average > 4 sources) on northern Mesopotamian sites during this time span. We argue that the Nemrut region was a major economic node and chief actor in the establishment and dynamics of networks in the greater region. The diachronic persistence or breaks in obsidian supply from more minor sources are an additional source of information on the inner workings and development of subtle interregional socio-political and economic relations. Obsidian analysis provides a detailed picture of the contributions of increasingly complex networks and channels of communication to intensified adoption of common practices and styles across regions, to intensification of processes leading to urbanization and state formation, and to accentuating periods of stress and conflict. These data nourish and update existing models on social networks during the crucial Ubaid to Late Chalcolithic periods and advance debates on the role and impact of these networks on early state formation. Highlights: 168 samples of archaeological obsidian from 12 Halaf-LC3 sites in Mesopotamia and the Arabian Gulf analyzed by LA-HR-ICP-MS These sites match many sources in eastern Anatolia and Armenia and varieties increase in the Ubaid and LC2 periods Matches show preponderance of obsidian from newly studied Sıcaksu outcrop of Nemrut Dağ across periods and regions treated Data suggests Nemrut was major economic actor in interaction networks of pre-state societies in ancient Near East